2016
DOI: 10.2147/ppa.s117757
|View full text |Cite
|
Sign up to set email alerts
|

The Australasian Hepatology Association consensus guidelines for the provision of adherence support to patients with hepatitis C on direct acting antivirals

Abstract: BackgroundHepatitis C is a blood-borne virus primarily spread through sharing of drug-injecting equipment. Approximately 150 million people worldwide and 230,000 Australians are living with chronic hepatitis C infection. In March 2016, the Australian government began subsidizing direct acting antivirals (DAAs) for the treatment of hepatitis C, which are highly effective (95% cure rate) and have few side effects. However, there is limited evidence to inform the provision of adherence support to people with hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 53 publications
4
15
0
Order By: Relevance
“…It is important to connect patients to social support organizations when needed. The involvement of pharmacies to provide daily doses for some patients, especially for those who are receiving opioid substitution therapy from community pharmacies, may improve patients’ adherence to treatment …”
Section: Discussionmentioning
confidence: 99%
“…It is important to connect patients to social support organizations when needed. The involvement of pharmacies to provide daily doses for some patients, especially for those who are receiving opioid substitution therapy from community pharmacies, may improve patients’ adherence to treatment …”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless they indicated it was important to acknowledge the potential for DAA side effects, as this would enable people to plan and establish contingency plans for the treatment course and support adherence. Overall, adherence to the DAAs was not an issue of concern, in this study, participants described how they identified their own memory hooks and existing routines to support the daily administration of the DAAs [ 31 ]. However, these participants were particularly motivated to achieve a cure.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence is defined by the WHO as “the extent to which a person’s behavior–taking medication, following a diet, and/or executing lifestyle changes–corresponds with agreed recommendations from a health care provider.” 58 Medication adherence, specifically, refers to the way patients take a prescribed medication, including the correct medication, dose, time, duration, as well as obtaining timely refills. 59 Medication adherence is particularly important in HIV, whereby poor adherence is associated with negative outcomes, including virologic failure and resistance. 60 Several interventions aimed at improving ART adherence have shown promise, 61 with those involving peer counseling and a mobile phone short message service delivery the most widely studied and implemented to date.…”
Section: Considering the Human Immunodeficiency Virus Care Cascade Asmentioning
confidence: 99%